Original paperDosimetric effects of prone and supine positions on post-implant assessments for prostate brachytherapy - Ohashi, Toshio; Momma, Tetsuo; Yamashita, Shoji; Kanai, Kunimitsu; Watanabe, Yusuke; Hanada, Takashi; Shigematsu, Naoyuki (Journal of Contemporary Brachytherapy, 2013)
Purpose: Post-implant dosimetric assessment is essential for optimal care of patients receiving prostate brachytherapy. In most institutions, post-implant computed tomography (CT) is performed in the supine position. This study aimed to assess variability in dosimetric parameters with postural changes during acquisition of post-implant CT scans. Material and methods: In total, 85 consecutive patients were enrolled in this study. Fifty-three patients underwent seed implantation alone, and the remaining 32 received a combination of seed implantation and external beam radiotherapy. For post-implant analyses, CT scans were obtained in two patient positions, supine and prone. To evaluate differences in dosimetric parameters associated with postural change, the dosimetric data obtained in the supine position were defined as the standard. Results: The median prostate volume was 22.4 ml in the supine and 22.5 ml in the prone position (p = 0.51). The median prostate D90 was 120.1% in the supine and 120.3% in the prone position, not significantly different. The mean prostate V100 was 97.1% in the supine and 97.0% in the prone position, again not significantly different. Median rectal V100 in supine and prone positions were 0.42 ml and 0.33 ml, respectively (p < 0.01). Rectal D2cc was also significantly decreased in the prone as compared with the supine position (median, 59.1% vs. 63.6%; p < 0.01). A larger post-implant prostate volume was associated with decreased rectal doses in the prone position. Conclusions : Though there were no significant differences among prostate D90 assessments according to postural changes, our results suggest that post-implant rectal doses decreased in the prone position.